2019
DOI: 10.1080/13670050.2019.1667949
|View full text |Cite
|
Sign up to set email alerts
|

It takes two to make a thing go write: self-reported Spanish reading and writing skill and relationships with digit span and stroop task performance among Spanish-English bilinguals

Abstract: The current study examined first language (Spanish) language reading and writing ability and behavior and relationships with digit span and stroop task performance. A battery of assessments and questionnaires was administered to 81 sequential Spanish-English bilingual university students in the U.S., for whom the sole language of education is English. . Hierarchical regression models revealed amount of Spanish used for academic writing uniquely accounted for 17% of variance in digit span forward scores, contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In addition, the multidimensional multifaceted nature of bilingualism calls for identifying the components which are relevant to multilingual profiles to develop research approaches where these components are related to specific linguistic and cognitive outcomes (Rothman et al, 2023). For instance, self-evaluated multilingual competence is identified as positively impacting text length in text production in elementary and secondary school children (Tolchinsky et al, 2022); self-reported amount of Spanish used for academic writing in Spanish-English bilinguals accounted for differences in short-term memory tasks (Smith and Briggs Baffoe-Djan, 2019). However, there is still no consensus as to which components of the bilingual profile must be measured.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the multidimensional multifaceted nature of bilingualism calls for identifying the components which are relevant to multilingual profiles to develop research approaches where these components are related to specific linguistic and cognitive outcomes (Rothman et al, 2023). For instance, self-evaluated multilingual competence is identified as positively impacting text length in text production in elementary and secondary school children (Tolchinsky et al, 2022); self-reported amount of Spanish used for academic writing in Spanish-English bilinguals accounted for differences in short-term memory tasks (Smith and Briggs Baffoe-Djan, 2019). However, there is still no consensus as to which components of the bilingual profile must be measured.…”
Section: Introductionmentioning
confidence: 99%